Development of Learning Methods for Student Center Learning with Problem Based Learning In Block 4.c "Midwifery Care in High Risk Childbirth and Postpartum" - Yulizawati Yulizawati; Miranie Safaringga; Ulfa Farrah Lisa; Rafika Oktofa (Faculty of Medicine, Universitas Andalas, 2019)
Achievement of the learning objectives of a student with the method of learning problem based learning (PBL), can be influenced by the results of extracting their peer information in small groups because the information obtained by students will be discussed to perfect the knowledge gained. This study applies a small group discussion (SGD) and tutorial in the PBL method. The results of the study, there was an increase in the value of students before and after treatment with a value of p = 0,000, and there was a difference in the grades of students in 2017 and 2016, where the grades of students in 2017 were better than in 2016, with p = 0.001. The results of the interview that students prefer the SGD method over discussion in large classes, students feel better understand the discussion material, each group member is more active and gives their opinions according to the theory of the book or journal that has been studied, lecturer attention to each student is greater, so students are very enthusiastic in studying the material and discussing it. PBL method with SGD is very effective to be applied in learning to increase the activeness, interactive, learning motivation, and critical thinking of students.